Burden, trends, and predictions of five major musculoskeletal disorders in China, Japan, and South Korea: analysis based on the Global Burden of Disease Study 2021 - Xinyue Yin; Tingting Deng; Rui Ma; Xiaomei Fu; Ying Yin; Xuemin Jia; Fanjie Liu (Frontiers in Public Health)
BackgroundMusculoskeletal disorders impose a heavy burden on society and the healthcare system. This study aims to describe the temporal trends of the burden of the top five musculoskeletal disorders in China, Japan and South Korea, assess their age, period and cohort effects, and predict the disease burden over the next 15 years.MethodsThe study utilized the Global Burden of Disease Study 2021 data. Key result metrics include the incidence, prevalence and disability-adjusted life years (DALYs) of gout, osteoarthritis, low back pain, neck pain and rheumatoid arthritis. Applying Joinpoint regression and age-period-cohort (APC) models to analyze temporal trends of five major musculoskeletal diseases from 1990 to 2021, considering age, period, and cohort effects. Future burden from 2022 to 2036 was forecasted using the autoregressive integrated moving average (ARIMA) model.ResultsFrom 1990 to 2021, the incidence of gout and osteoarthritis in China increased by 160.5 and 150.4%, respectively, with Japan’s gout incidence up by 65.3% and South Korea’s gout and rheumatoid arthritis rates rising by 165.0 and 164.6%. The burden of these diseases, except for gout, was higher in female. The risk of musculoskeletal diseases increases with age and recent birth cohorts. The impact of high body mass index (BMI) on gout, low back pain, and osteoarthritis is escalating. By 2036, the disease burden is expected to remain heavy, with varying degrees of increase.ConclusionThe burden of the five musculoskeletal diseases in China, Japan, and South Korea is significant. There is a particular need to pay close attention to the increasingly severe impact of older adult female populations and high BMI on gout, low back pain, and osteoarthritis. It is recommended that governments increase investment and implement prevention strategies, including weight management and health education.